Creating a conceptual framework to improve the re-usability of open geographic data in cities - Comber, A. (2020)
The essential elementsdefined in this research are the definition of data user communitiesand their needs, the creation of the community of reuse, user-focusedmetadata, and reuse-focused legal terms. The definition of these indi-cators provides a framework for authorities to re-shape their currentopen data strategy to include data user requirements. At the end ofthis article, a roadmap for future research and implementation is pre-sented, considering some reflections on the conceptual framework.